Dampak Iklim terhadap Kejadian Diare Balita di Negara Tropis: Literature Review - Rizsa Fauziah Ichwani; Ema Hermawati (Universitas Muhammadiyah Semarang, 2022)
Background: Diarrhea globally continues to be the second top infectious disease leading to death in children under five years of age. Climate change that occurs affects meteorological conditions where this condition provides opportunities for diarrheal pathogens to increasingly transmit and infect humans. Especially tropical countries which are considered to have a higher risk compared to other types of climate, this is because climate variations that do not vary allow diarrhea transmission to occur throughout the year. The immune system of toddlers, which in fact is not as good as adults, causes a higher chance of being infected with diarrhea. Methods: Using literature review method that analyzes meteorological risk factors for the incidence of diarrhea in children under five. Results: Air temperature has implications for diarrhea both at high and low temperatures. In addition, high humidity is known to increase cases of diarrhea in toddlers due to rotavirus. Moderate to high rainfall during the previous 1 to 3 weeks can also increase cases of diarrhea in children under five. On the other hand, low access to piped water when the air temperature is high is known to be associated with high cases of diarrhea. Conclusion: Air temperature, humidity and high rainfall in tropical countries can increase the potential for toddlers to be infected with diarrhea. In addition, low water access when the air temperature is high can contribute to a higher incidence of diarrhea in children under five.